2018
DOI: 10.3168/jds.2017-13778
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of topical treatments for mild and severe udder cleft dermatitis in Dutch dairy cows

Abstract: Udder cleft dermatitis (UCD) is a skin lesion in dairy cows affecting the anterior parts of the udder, with the lesions often needing a long time to heal. The lesions can be characterized as mild or severe. The etiology of UCD is not fully understood and studies on the effectiveness of topical treatments have not been published. The objective of this study, therefore, was to conduct a randomized clinical trial to investigate the effectiveness of 2 different topical treatments, one for mild and one for severe U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…In our study, udder cleft dermatitis lesions were histopathologically often characterized by a chronic or chronic active inflammation. This chronic character is in line with the studies of Bouma et al (2016) andvan Werven et al (2018). This last study showed that even intensive treatment for a long period had limited results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, udder cleft dermatitis lesions were histopathologically often characterized by a chronic or chronic active inflammation. This chronic character is in line with the studies of Bouma et al (2016) andvan Werven et al (2018). This last study showed that even intensive treatment for a long period had limited results.…”
Section: Discussionsupporting
confidence: 87%
“…However, this was not supported by a recent study by Sorge et al (2019), in which the authors concluded that it seemed unlikely that spirochetes play a major role in the development of UCD. Although a bacteriological cause of UCD lesions is not yet known, farmers often treat the lesions with sprays or ointments containing antimicrobial agents (van Werven et al, 2018). Presence of bacteria other than treponemes in UCD lesions was described in a recent study using a metagenomic approach (Sorge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…All treatments were applied by trained veterinary students. Upon recruitment (d 0), on all farms but one, the hind feet of all lactating cows were given a foot trim according to the Dutch 5-step method (Toussaint Raven, 1989) by the herd's regular hoof trimmer, and all feet of these cows were given an M-score by a trained veterinary student. On one farm (farm 1), the farmer selected 43 cows (out of 118 lactating cows) for foot trimming, because they were lame, likely to have an active DD lesion, or both.…”
Section: Treatment Protocolmentioning
confidence: 99%
“…Since its first introduction, novel products and strategies have emerged to aid in achieving the TIME principle, with enzymatic alginates being one of them. Recently, an enzyme alginogel has appeared effective in the treatment of udder cleft dermatitis, an ulcerative dermatitis, in dairy cows (van Werven et al, 2018). Alginates are known for their capacity to absorb debris and exudate (passive debridement) and for keeping wounds moist through their gelling capacity (moisture balance; Strohal et al, 2013;Jacobsen, 2017;Jones and Oates, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to anecdotal reports, treatment strategies for severe UCD tested by Swedish farmers include cleaning with soap, iodine, or hydrogen peroxide; application of potato flour or honey; and spraying with chlortetracycline spray, as well as various combinations of these methods and other wound products (L. Ekman, unpublished data). A recent Dutch study that tested a topical enzyme alginogel on severe UCD lesions found that the alginogel improved healing of the lesions (van Werven et al, 2018). Enzyme alginogels are used in the care of human pressure ulcers, which, not unlike UCD lesions, often have a long duration and delayed healing (van Werven et al, 2018).…”
Section: Introductionmentioning
confidence: 99%